Care partner evaluation of the behaviors in the Cohen-Mansfield Agitation Inventory - Oberdhan, Dorothee; Palsgrove, Andrew; Houle, Christy; Lovell, Teya; Levine, A. Alex; Frangiosa, Terry; Biggar, Ginny; Comer, Meryl (Frontiers in Dementia, 2024)
Introduction Agitation is a common symptom in patients with Alzheimer's dementia. But agitation can be a heterogeneous symptom, encompassing a diverse array of behaviors exhibited by patients. The Cohen-Mansfield Agitation Inventory (CMAI) is a 29-item scale that is used to systematically assess the frequency and severity of agitation in older adults as rated by a primary caregiver. The CMAI was originally designed for use by professional care givers in institutional care settings. Alzheimer's dementia, however, is associated with a significant burden on family members, who provide the majority of care, and other informal care partners. Methods Our qualitative study aimed to assess the accuracy and applicability of the CMAI according to the needs and perceptions of non-professional care partners. Specifically, we wanted to determine if the behaviors included in the instrument reflect: (a) the care partner's experience with agitation in Alzheimer's dementia patients, (b) how the behaviors and their frequency are related to the perception of agitation severity, and (c) what changes in agitation behaviors are meaningful to care partners. We interviewed 30 care partners for patients with Alzheimer's dementia in the United States. Results The care partners confirmed all behaviors listed in the CMAI as relevant. The behaviors reflect a spectrum of severity, with aggressive behaviors considered more severe than non-aggressive behaviors and physical behaviors generally considered more severe than verbal behaviors. Any reduction or increase in the frequency of a behavior was meaningful to care partners. Generally, a change from physical to verbal behaviors and aggressive to non-aggressive was considered a meaningful improvement while a change from verbal to physical and non-aggressive to aggressive was considered a meaningful worsening. Discussion The CMAI appropriately captures relevant behaviors of agitation in Alzheimer's dementia and provides insight into the relative improvement or worsening of agitation symptoms.